Pencegahan dan Promosi Kesehatan Gigi Bagi Siswa Sekolah Dasar Negeri Di Desa Kukuh Kecamatan Marga Tabanan Tahun 2018 - Ni Nyoman Dewi Supariani; I Nyoman Gejir; Ida Ayu Dewi Kumala Ratih; Asep Arifin Senjaya (Jurnal Pengabmas Masyarakat Sehat, 2019)
In Indonesia there was an increase in the prevalence of dental caries in the Indonesian population compared to 2007, namely from 43.4% in 2007 to 53.2% in 2013. Caries and periodontal disease were the most common dental and oral diseases suffered by school-age children. One group that is vulnerable to caries. Plaques contribute to the pathogenicity of caries and periodontal disease. Brushing your teeth is the main action for cleaning plaque. Dental and oral health education is a method to motivate patients to clean their mouth effectively. Providing prevention and promotion of dental health in the teeth of elementary school students in Kukuh Village, Marga Tabanan District. The realization of the activity was counseling and brushing mass teeth three days in a row at Kukuh Village Elementary School. The paired T test for the pre and posttest values indicates the sig value. 0,000. Counseling brushing teeth is significant towards increasing student knowledge. Suggestions that can be given are: Puskesmas officers can carry out dental and oral health education activities for elementary school students in their working area, on an ongoing basis.Keyword: prevention, dental health promotion